Peningkatan pengetahuan pada masyarakat tentang konstruksi sumur gali dan bak penampungan limbah serta jarak yang aman terhadap sumber pencemar - Darmiati Darmiati; Nilawati Nilawati (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: The use of mercury material has developed very broadly, and one of them is in the gold mining process which is carried out in the gold extraction process. The activity is carried out in the yard of the house and adjacent to the dug well, this can cause pollution in the soil and dug well water. Problems that arise due to exposure to Mercury are gastrointestinal disorders, kidney damage, nerve damage, disability in the fetus, while in children will reduce cognitive abilities and thinking, memory, attention, language mastery, fine motor skills and visual.Objectives: The purpose of this community service is to increase community knowledge about the construction of dug wells and waste collection tanks as well as a safe distance to pollutants in the traditional gold mining.Method: The study used a cross-sectional design, involving subjects in 30 community groups. Data collection using a questionnaire and conducted interviews. Analysis of research data is only done univariately.Results: The results of the evaluation of the activity revealed that there was an increase in public knowledge of the conditions for the construction of dug wells, waste collection basins and diseases caused by mercury exposure directly or indirectly on the human body (able to answer questions correctly more than 20% on each question item).Conclusion: Most people begin to understand that the danger of mercury does not only occur in the skin, but can affect the entire organ system and permanent nervous system damage.